Establishment of an Ex Vivo Inflammatory Osteoarthritis Model With Human Osteochondral Explants - Li, Kaihu; Zhang, Penghui; Zhu, Yong; Alini, Mauro; Grad, Sibylle; Li, Zhen (Frontiers in Bioengineering and Biotechnology, 2021)
Osteoarthritis (OA) is the most common degenerative joint disease without clear pathophysiological mechanism and effective drugs for treatment. Though various animal models exist, the translation of the outcome into clinics remains difficult due to species differences. In this study, an ex vivo inflammatory OA model was induced using different concentrations of interleukin 1 beta (IL-1β) and tumor necrosis factor α (TNF-α) on explants from human femoral head. In the inflammatory OA groups, the gene expression levels of cartilage catabolism (matrix metalloproteinase 1 (MMP1), matrix metalloproteinase 3 (MMP3)), and inflammation (interleukin 6 (IL-6), interleukin 8 (IL-8)) markers were significantly upregulated, while the anabolic genes (collagen 2 (COL2), aggrecan (ACAN), proteoglycan 4 (PRG4)) were downregulated compared to the control group. The release of cytokines (IL-6, IL-8) and nitric oxide (NO) in conditioned medium was also upregulated in inflammatory OA groups. The Safranin O/Fast Green staining showed loss of proteoglycan in the superficial zone cartilage after cytokine treatment. The results indicated that an ex vivo inflammation and degeneration model was successfully established using osteochondral explants from human femoral head. This model can be used to elucidate the in-depth mechanism of inflammatory OA, and to screen new drugs for treatment.